PENERAPAN TEKNOLOGI AUGMENTED REALITY PADA KATALOG PRODUK BERBASIS ANDROID STUDI KASUS CV. JINGGA CIPTA PERSADA GROUP - Muhammad Noval Riswandha; Mochammad Fahrur Rozi (SPIRIT, 2022)
Abstract : The existence of this digital development provides space to implement Augmented Reality (AR) on CV. JINGGA CIPTA PERSADA GROUP SIDOARJO which is engaged in the printing sector that has collaborated with educational institutions, government agencies and government agencies which have been serving their customers for almost 21 years. Augmented Reality (AR) delivery has its own charm. Augmented Reality (AR) can present a menu of catalog and a selection of product results from CV. JINGGA CIPTA PERSADA GROUP with a more attractive and interactive way to buyers. With the Augmented Reality (AR) catalog, without the need to move from one site to another, and / or from one application to another, you can even add some amazing features which will certainly be of value for the business development of the CV company. CV. CIPTA PERSADA GROUP. One of the projects that will be implemented in CV. JINGGA CIPTA PERSADA GROUP is the application of Augmented Reality (AR) in the marketing business. To support this, of course, a plan is needed for the implementation of Augmented Reality (AR) which uses the Marker Based Tracking method and the catalog as object tracking. The Marker Based Tracking method itself is a marker used in planning for the implementation of Augmented Reality (AR). This arrangement is based on objectives as a CV business progress. CV. CIPTA PERSADA GROUP. This research will produce the main output, namely a promotional media. Through the research results will be obtained in the form of an Augmented Reality application CV catalog. JINGGA CIPTA PERSADA GROUP which can be shortened to "ARJingga" using the Android-based Marker Based Tracking method